The Effects of Cognitive-Affective Switching With Unpredictable Cues in Adults and Adolescents and Their Relation to “Cool” Executive Functioning and Emotion Regulation - Samson, Jessica L.; Rochat, Lucien; Chanal, Julien; Badoud, Deborah; Perroud, Nader; Debbané, Martin (Frontiers in Psychology, 2022)
The impact of emotion on executive functioning is gaining interest. It has led to the differentiation of “cool” Executive Functioning (EF) processes, such as cognitive flexibility, and “hot” EF processes, such as affective flexibility. But how does affective flexibility, the ability to switch between cognitive and affective information, vary as a function of age and sex? How does this construct relate to “cool” executive functioning and cognitive-emotion regulation processes? In this study, 266 participants, including 91 adolescents (M=16.08, SD=1.42 years old) and 175 adults (M= 25.69, SD= 2.17 years old), completed a cognitive-affective switching task with specific (as opposed to general) unpredictable switches, as well as measures of inhibition, attention, and cognitive-emotion coping strategies. We expected cognitive to affective switching to be more costly than affective to cognitive switching in females versus males , as well as higher switch costs in adolescents. Using linear mixed modelling, we analysed the effect of age, sex, and types of switching on reaction time. Results show that adolescents are slower switchers than adults, and demonstrate that females, although faster switchers than males, are slower when switching from cognitive to affective content than when they are switching from affective to cognitive content. Multiple regression analyses revealed age-specific associations between cognitive-affective switching and inhibition. These results converge with reported developmental and gender specificities in EF and emotion processing, respectively. Additionally, affective flexibility could relate to differences in vigilance and inhibition.